To develop a GPS (Global positioning system) AVL (automatic vehicle locator) tracking system - Khurshid, Imran Newaz; Rabbi, SK. Adnan; Azad, Md. Abul Kalam; Ruhullah, Ahmed Tanjil (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2010.